Effects on and adaptation of the family context during the COVID-19 pandemic. Some remarks from Italy and Mexico. Issue 1 (2nd January 2022) - Bianchi, Francesca; Martínez Núñez, Maria Teresa de Jesús; Nájera, Estefanía Villarreal; Calderón Garza, Olga Catalina
ABSTRACT: The first COVID-19 case in Italy was registered on 21 February 2020, thrusting Italy into a state of emergency which quickly produced burdensome economic and social effects. In this contribution we choose to reflect on how social institutions, family and school have been reacting to the pandemic. We will try to analyse the main changes that occurred regarding educational and family institutions in Italy and Mexico, two countries that show numerous similarities with respect to both the inequalities present in families and the school learning process and their reactions to the crisis. In both countries the pandemic has demonstrated the great resilience of families, but there are also social, economic, cultural and educational inequalities that force us to deeply rethink the cultural and social development models of the two countries.